A comprehensive study of cytosine-ZnO interactions: Theoretical and experimental insights - Bulut, Niyazi; Keser, Serhat; Zanchet, Alexandre; Zuchowski, Piotr S.; Ates, Tankut; Kilic, Irfan; Kaygili, Omer (Elsevier, 2025)
This paper presents a comprehensive investigation of the adsorption of cytosine, a DNA base, on ZnO model clusters, specifically Zn2O2, Zn3O3, Zn4O4, Zn6O6, Zn8O8 ring (R) and cubic rocksalt. A density functional theory (DFT) method was used to simulate the adsorption of cytosine on ZnO (C/ZnO) clusters. The B3LYP/LanL2DZ method, which includes a correction for the dispersion contribution, was used. The calculated energy gap (Eg) for cytosine showed a strong dependence on the cluster size, highlighting variations corresponding to the dimensions of the clusters. The proposed physisorption mechanism involves the formation of an N...Zn bond between cytosine and the active Zn site on ZnO. In addition, experimental data, including microscopic and spectroscopic evidence, were integrated to further elucidate the interactions between cytosine and ZnO. A composite of C and ZnO was prepared by the wet chemical method and characterised by SEM, XRD and FT-IR analyses. The interaction of cytosine with ZnO nanoparticles was observed by UV-vis spectroscopy. The experimental results were then compared with those obtained from DFT calculations, taking into account the new insights into the cytosine-ZnO interactions. This comparison provided a holistic understanding of the system.
Keywords: Zinc oxide (ZnO); Cytosine; Density functional theory (DFT)